2021
DOI: 10.1177/00491241211009946
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the “Grievance Studies Affair” Papers and Why They Should Be Reinstated: A Response to Geoff Cole

Abstract: In April, 2020, Dr. Geoff Cole published, “Why the ‘Hoax’ Paper of Baldwin (2018) Should Be Reinstated.” We are the authors of the “Baldwin” paper published in Fat Studies. The paper satirized theoretical ideas within Fat Studies as part of a larger project to demonstrate the lack of rigor in certain theoretical approaches to cultural studies. In this response, we agree with Cole that our project should not be understood as hoaxes and that the retracted article should be reinstated, but defend our methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Third, subscription-based journals may have problems ensuring quality and scientific rigour. It was demonstrated in a recent exercise in which three authors submitted 20 papers to established journals that they had written specifically to use fashionable terminology but were worthless in terms of their academic content: seven were accepted (Pluckrose et al, 2021). Moreover, it has been found that even the most reputable indexes (such as Scopus) have been accepting large numbers of predatory journals (Chawla, 2021).…”
Section: Possible Disadvantages Of the Oa Modelmentioning
confidence: 99%
“…Third, subscription-based journals may have problems ensuring quality and scientific rigour. It was demonstrated in a recent exercise in which three authors submitted 20 papers to established journals that they had written specifically to use fashionable terminology but were worthless in terms of their academic content: seven were accepted (Pluckrose et al, 2021). Moreover, it has been found that even the most reputable indexes (such as Scopus) have been accepting large numbers of predatory journals (Chawla, 2021).…”
Section: Possible Disadvantages Of the Oa Modelmentioning
confidence: 99%
“…The result is that caste studies has degenerated into the same rot more generally acquired by grievance studies. This leads to some embarrassing events such as the "Sokal Squared" affair (Pluckrose et al 2018(Pluckrose et al , 2021 that exposed how bogus research sneaks past review processes as long as the rhetoric employed by the authors remains within the bounds of approved clichés and the favoured victim group is shown as consistently oppressed, whatever their actual condition. One can't help thinking that caste studies rely on yet another fallacy: the appeal to the emotion of pity (Wrisley 2019).…”
Section: Caste Studies Degeneratedmentioning
confidence: 99%
“…A major thrust of the commentary (Pluckrose, Lindsay, and Boghossian 2021) is the argument that the so-called grievance studies project was not a hoax. A hoax paper, according to the authors, includes information that is almost entirely nonsense (e.g., Sokal 1996).…”
Section: Was the Grievance Studies Project A “Hoax”?mentioning
confidence: 99%